2022
DOI: 10.1186/s12882-022-02813-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing acute presentations of atheromatous renal artery stenosis

Abstract: Background Atherosclerotic renovascular disease (ARVD) often follows an asymptomatic chronic course which may be undetected for many years. However, there are certain critical acute presentations associated with ARVD and these require a high index of suspicion for underlying high-grade RAS (renal artery stenosis) to improve patient outcomes. These acute presentations, which include decompensated heart failure syndromes, accelerated hypertension, rapidly declining renal function, and acute kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…According to observational studies and several case reports, a high proportion of patients in an acute setting improves after PTRA, with possible normalisation of renal function. 13 20 Furthermore, the rapidity of decline in renal function – which suggests the absence of an irreversible chronic parenchymal damage – is reported to be a good prognostic factor after PTRA. 10 , 30 , 31 A low urine albumin/creatinine ratio (<22.5 mg/g or <2.25 mg/mmol) has also been reported to be a good prognostic factor after PTRA 32 (note, however, that our patient, who was diabetic, had a much higher UACR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to observational studies and several case reports, a high proportion of patients in an acute setting improves after PTRA, with possible normalisation of renal function. 13 20 Furthermore, the rapidity of decline in renal function – which suggests the absence of an irreversible chronic parenchymal damage – is reported to be a good prognostic factor after PTRA. 10 , 30 , 31 A low urine albumin/creatinine ratio (<22.5 mg/g or <2.25 mg/mmol) has also been reported to be a good prognostic factor after PTRA 32 (note, however, that our patient, who was diabetic, had a much higher UACR).…”
Section: Discussionmentioning
confidence: 99%
“… 9 13 In acute settings with rapidly progressive heart and renal failure, BMT versus revascularisation has been only rarely studied and some observational studies have shown improved outcomes in patients who underwent percutaneous transluminal renal angioplasty (PTRA) and stenting of the RAS. 13 20 Indeed, some subgroups of patients, including patients with a solitary functioning kidney, 20 23 could benefit from this more interventional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to identify ARAS promptly can result in progressive deterioration of renal function, end-stage renal disease, and refractory hypertension. Early screening, intervention, and treatment are crucial in preventing the development of ARAS into end-stage renal disease 4 .…”
Section: Introductionmentioning
confidence: 99%